2008
DOI: 10.1080/10715760801993076
|View full text |Cite
|
Sign up to set email alerts
|

Protection of chlorophyllin against oxidative damage by inducing HO-1 and NQO1 expression mediated by PI3K/Akt and Nrf2

Abstract: Green vegetables are thought to have a chemoprotective effect on the basis of epidemiologic evidence. This study investigated whether chlorophyllin (CHL) could induce antioxidant enzymes and confer protection against oxidative damage. The results showed that CHL could induce HO-1 and NQO1 expression in human umbilical vein endothelial cell (HUVEC) in a time- and dose-dependent manner and protect them against hydrogen peroxide caused oxidative damage. The induction of HO-1 and NQO1 by CHL was accompanied with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 40 publications
1
39
1
Order By: Relevance
“…This finding is supported by previous reports that HG induced TGF-β generation [11] and that TGF-β1 up-regulated HO-1 expression via the PI3K/Akt signaling pathway [43]. However, our results are inconsistent with previous observations that ROS induced an increase in HO-1 expression via the PI3K/Akt signaling pathway in other cells type [56,57], which may be due to specific cell types or other factors. We cannot resolve this problem in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is supported by previous reports that HG induced TGF-β generation [11] and that TGF-β1 up-regulated HO-1 expression via the PI3K/Akt signaling pathway [43]. However, our results are inconsistent with previous observations that ROS induced an increase in HO-1 expression via the PI3K/Akt signaling pathway in other cells type [56,57], which may be due to specific cell types or other factors. We cannot resolve this problem in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the mechanisms of activation are only partially understood. A candidate signaling molecule is PI3K, which is well characterized as an important mediator of biological activity of OxPLs ( 20,21 ) and, on the other hand, has been shown to play a critical role in the induction of NRF2 and NRF2-dependent genes in response to oxidative stressors and electrophilic compounds ( 7,(22)(23)(24). Based on these data, we asked whether PI3K plays a role in activation of electrophilic stress by OxPLs.…”
Section: Resultsmentioning
confidence: 99%
“…We had earlier shown that chlorophyllin enhanced the expression of antiapoptotic genes in the lymphocytes and thereby modulated lymphocyte homeostasis and immune responses in vivo [21]. Chlorophyllin has also been shown to activate the pro-survival transcription factor Nrf-2 in human umbilical vein endothelial cells and prevent oxidative stress induced apoptosis in vitro [35]. In the present investigations, it was revealed that chlorophyllin not only modulated the abundance and proliferation of HSPC but also enhanced the recovery from radiation induced bone marrow aplasia and lymphopenia.…”
Section: ϯϭmentioning
confidence: 97%